2022
DOI: 10.1177/07067437221097906
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Cohort Study of Youth Mental Health and Substance use Before and During the COVID-19 Pandemic in Ontario, Canada: An Exploratory Analysis

Abstract: Background Youth mental health appears to have been negatively impacted by the COVID-19 pandemic. The impact on substance use is less clear, as is the impact on subgroups of youth, including those with pre-existing mental health or substance use challenges. Objective This hypothesis-generating study examines the longitudinal evolution of youth mental health and substance use from before the COVID-19 pandemic to over one year into the pandemic among youth with pre-existing mental health or substance use challen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Substance use‐related ED visits among adolescents and young adults have decreased by 1.5 times during the pandemic compared to the prepandemic level in Ontario, Canada. This finding aligns with existing literature reporting a reduced volume of substance use‐related ED visits during the COVID‐19 pandemic 11,12,28,33,39–42 . This overall reduction in 2020 may reflect an increased threshold for seeking hospital care due to anxiety surrounding COVID‐19 exposure and the enactment of healthcare policies that prioritized urgent visits and delayed/ceased elective care.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Substance use‐related ED visits among adolescents and young adults have decreased by 1.5 times during the pandemic compared to the prepandemic level in Ontario, Canada. This finding aligns with existing literature reporting a reduced volume of substance use‐related ED visits during the COVID‐19 pandemic 11,12,28,33,39–42 . This overall reduction in 2020 may reflect an increased threshold for seeking hospital care due to anxiety surrounding COVID‐19 exposure and the enactment of healthcare policies that prioritized urgent visits and delayed/ceased elective care.…”
Section: Discussionsupporting
confidence: 87%
“…This finding aligns with existing literature reporting a reduced volume of substance userelated ED visits during the COVID-19 pandemic. 11,12,28,33,[39][40][41][42] This overall reduction in 2020 may reflect an increased threshold for seeking hospital care due to anxiety surrounding COVID-19 exposure and the enactment of healthcare policies that prioritized urgent visits and delayed/ceased elective care. It is worth noting that as the public safety measures lifted, 2,3 the rate of presentations slowly increased in 2021, in line with other studies reporting a similar trend of volume recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of COVID-19, the GAIN-SS survey has been used to investigate behavioral differences between students and nonstudents [ 28 ]. Findings demonstrated that MH issues were stable but substance use declined in youths during the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…As for addiction, a decline in substance use has been reported, especially among adolescents initially at higher risk for substance use disorder. 21 , 22 It is clear from these limitations that longitudinal trajectory research with comprehensive mental health assessments, spanning the pre-pandemic period and across multiple lockdown and release phases, is needed to understand the long-term impact of the COVID-19 pandemic on youth mental health. 13 Research comparing data from the general population and from patient groups is also needed.…”
mentioning
confidence: 99%